Existence and Uniqueness Results for a Smooth Model of Periodic Infectious Diseases - Guy Degla (Abstract and Applied Analysis)
We prove the existence of a curve (with respect to the scalar delay) of periodic positive solutions for a smooth model of Cooke-Kaplan’s integral equation by using the implicit function theorem under suitable conditions. We also show a situation in which any bounded solution with a sufficiently small delay is isolated, clearing an asymptotic stability result of Cooke and Kaplan.